Generalised Hyers-Ulam Product-Sum Stability of a Cauchy Type Additive Functional Equation (European Journal of Pure and Applied Mathematics, 2011)
In 1940 (and 1964) S.M. Ulam proposed the well-known Ulam stability problem. In 1941 D.H. Hyers solved the Hyers-Ulam problem for linear mappings. In 2008, J. M. Rassias introduced the generalised Hyers-Ulam "product-sum" stability. In this paper we introduce a Cauchy type additive functional equation and investigate the generalised Hyers-Ulam "product-sum" stability of this equation.